Frontiers in Periodontology (IntechOpen, 2025)
This book offers a comprehensive overview of emerging advancements in the management of periodontal and peri-implant diseases, providing crucial insights for clinicians and researchers alike. It explores the potential of probiotics in restoring oral microbiome balance and investigates the future applications of epigenetics and stem cell therapies in periodontal regeneration. The book highlights innovative technologies, such as three-dimensional printing and diode laser therapies, poised to enhance diagnostic precision and therapeutic outcomes. Emphasizing minimally invasive, non-surgical treatments and novel non-invasive indices for evaluation, this volume advocates for safer and more effective approaches to periodontal care and will serve as an essential resource for advancing clinical practice and research in periodontology.